Sleepers Book Shop And Rented Cafe / Faizal Mhd Sarif ... [et al.] - Mhd Sarif, Faizal; Fuad, Nurnajwa; Yusoff, Zamilah; Hamzah, Haryani; Hassan, Juni Farhana; Jamaludin, Sitt Norafidah (Faculty of Electrical Engineering, 2002)
Sleepers book store and rented is a partnership business, which register under Register of Business. The business would be operation on year 2003. The sleeper's bookstore is open with a hope that this store will attract Malaysians who are interested in reading.